Z lego gradniki razvijamo računalniško mišljenje pri predšolskih otrocih - Cesarec, Anja (Revija inovativna pedagogika, 2025)
Preschool children used LEGO bricks to develop computational thinking through various play-based activities without using a computer. Through play, children acquired key skills, such as problemsolving, logical thinking, and sequencing skills. The use of LEGO bricks has proved highly motivating for the children, as they have been involved in the activities for a more extended period of time. First, they familiarized themselves with the expressions used to describe the positioning of an object and learned how to orient themselves in space. The children developed computational thinking through various activities, introducing the concepts of sequences, instruction following, and pattern recognition. We found that, with or without LEGO bricks children unknowingly acquire computational thinking skills through play. In addition, children noticeably progressed and obtained computational skills at a different pace, i.e., the amount of time required to acquire the skill differed. In this case, repetitive tasks based on supportive feedback and encouragement are crucial for the child to finish a task successfully.
Keywords: computational thinking; LEGO (igrače); LEGO bricks; lego gradniki; orientacija v prostoru; Predšolska vzgoja; Predšolsko učenje in poučevanje; prostorski odnosi; računalniško mišljenje; Računalništvo; spatial orientation; spatial relations